Digital Technology as A Driver of Government Efficiency: An Analysis of Government Parastatals in Lagos State, Nigeria - Solomon Adejare Babarinde (PERSPEKTIF, 2024)
Digital technology is fast becoming a global phenomenon for efficient service delivery, both in private and public institutions. Developing nations have been increasing their investments in essential E-government administration systems. Therefore, this study examined the role of digital technology in driving government efficiency among parastatals in Lagos, Nigeria. A structured questionnaire on the study variables was developed and a descriptive survey research approach was used to harvest information from employees of five purposively selected government parastatals in Lagos state. Three hundred and eighty-seven copies of the questionnaire were properly filled and the data was presented using frequency tables and percentages. The Kruskal-Wallis test and OLS regression technique were used for the inferential analysis. The result of the analysis revealed that digital technology significantly influences record management, speed of service delivery, and service provision amongst government parastatals. The study concludes that digital technology is a major driver of government efficiency. The study recommends that the government should invest in creating critical digital enablers and providing incentives to encourage their widespread use across their establishments.